The value of extracurricular activities to Japanese junior high school students: focusing on the expression of a school’s attractiveness in writing - Onoda, Ryosuke; Omi, Yasuhiro (Frontiers in Education, 2023)
This study explores the value of extracurricular activities to Japanese junior high school students and how this value can be transmitted to junior students through essay writing. The study participants involved Japanese seventh graders; the essay focused on school attractiveness and covered the following three conditions: (1) "control condition," where juniors (sixth graders) are assumed to be readers, (2) "emphasis condition," where the teacher requested participants to assume a more specific view of the juniors, and (3) "emphasis-visualization condition," where the teacher requested participants to assume a more specific view of juniors and where the participants visualized the characteristics of juniors before completing the writing assignment. More information regarding extracurricular activities was provided in the emphasis-visualization condition. This suggests that when Japanese junior high school students are highly aware of their juniors, they evaluate extracurricular activities as an attractive school feature and readily transmit this value to younger students.